2012
DOI: 10.1021/am3020372
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Highly Efficient Preconcentration of Eu(III) by Core–Shell Structured Fe3O4@Humic Acid Magnetic Nanoparticles

Abstract: In this study, humic acid-coated Fe(3)O(4) magnetic nanoparticles (Fe(3)O(4)@HA MNPs) were synthesized using a chemical coprecipitation method and characterized in detail. The XRD analysis results showed that HA coating did not change the phase of Fe(3)O(4) cores. The TEM image suggested that Fe(3)O(4)@HA MNPs had nearly uniform size without the observation of aggregation. The Fe(3)O(4)@HA MNPs were stable in solution and could be easily separated from aqueous solution using a magnetic separation method. A bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(99 citation statements)
references
References 56 publications
5
92
0
2
Order By: Relevance
“…Humic acid (HA) coated Fe 3 O 4 nanoparticles were synthesized by co-precipitation method [98] leading to a core-shell type structure. The Fe 3 O 4 @HA particles appeared as spheroidal shaped with nearly uniform sizes.…”
Section: Magnetic Bionanocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Humic acid (HA) coated Fe 3 O 4 nanoparticles were synthesized by co-precipitation method [98] leading to a core-shell type structure. The Fe 3 O 4 @HA particles appeared as spheroidal shaped with nearly uniform sizes.…”
Section: Magnetic Bionanocompositesmentioning
confidence: 99%
“…Table 4 lists the most representative isotherm and kinetic equations used for describing the adsorption of water pollutants. The Langmuir equation [47] derives from an isotherm model commonly applied to describe the equilibrium of sorption on magnetic bionanocomposites [60,40,81,102,14,104,59,98,94,26]. This empirical model assumes monolayer adsorption at a finite number of sites that are identical and equivalent, without any interaction between molecules adsorbed on adjacent sites.…”
Section: Modeling the Adsorption Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this point, environmentalists synthesized humic acid-coated Fe 3 O 4 magnetic nanoparticles (Fe 3 O 4 @HA MNPs) as an adsorbent to evaluate its removal efficiency towards Eu(III) under various environmental conditions. 77 The kinetic studies showed that Eu(III) adsorption onto The synthesized adsorbent showed good recycling performance up to six cycles using 0.01 M HCl solution as an eluent. Based on the negligible leachability of Eu from the loaded adsorbent in tap water over a period of three months, the Fe 3 O 4 @HA MNPs was proposed as a highly effective material for the enrichment and pre-concentration of radionuclide Eu(III) or other trivalent lanthanides/actinides in geological repositories or in nuclear waste management.…”
mentioning
confidence: 93%
“…Thereby, the research on the interaction of 152?154 Eu(III) with different kinds of oxides, clay minerals or manmade nanomaterials is important to understand the physicochemical properties of other trivalent lanthanides or actinides in the environment. The sorption of 152?154 Eu(III) on clay minerals, metal oxides and nanomaterials had been extensively studied in the last decade [7][8][9][10][11][12][13][14][15][16][17], and the results suggested that the sorption of Eu(III) was strongly dependent on ionic strength and pH at low pH values. The sorption was mainly dominated by outer-sphere surface complexation and/or ion exchange at low pH, and by inner-sphere surface complexation and/or surface (co)precipitation at high pH values.…”
Section: Introductionmentioning
confidence: 99%